The Association Between Sleep Quality, Depression, Anxiety, and Job-related Stress Among Nurses in Saudi Arabia - Mostoles, Romeo Jr Patague (UI Scholars Hub, 2024)
Background: This study examined the mediating role of sleep quality in the relationship between depression, anxiety, and job-related stress among nurses in Saudi Arabia. Methods: Sociodemographic information, Pittsburgh Sleep Quality Index, depression, anxiety, and work-related stress were evaluated in 851 nurses. Structural equation modeling was used to investigate the mediation effect of sleep quality on mental health and job stress in nurses. Results: High rates of anxiety (65.9% severe, 34.1% moderate), depression (37.2% moderate to severe), and poor sleep (51.4%) were found. Sex, marital status, education, nationality, and smoking status significantly influenced mental health outcomes. For example, female, college-educated, non-Saudi, and smoker participants reported lower depression levels. Younger participants (aged 26–35) were associated with higher anxiety and lower poor sleep. Conclusions: This study revealed a significant prevalence of anxiety, depression, and sleep disturbances among nurses. Females and those with lower education levels and in specific age groups were more likely to experience poorer mental health. Poor sleep quality was strongly associated with anxiety and depression. These findings indicate the urgent need for comprehensive mental health assessments and interventions to improve the well-being of nurses.